Job stress and needlestick injuries in nurses: a retrospective observational study: Job stress and needlestick injuries in nurses - d'Ettorre, Gabriele; Greco, Mariarita (Acta Biomedica Atenei Parmensis, 2020)
Background: The prevention of needlestick injuries (NSIs) in nurses employed in Emergency Departments (EDs) represents a special issue for healthcare organizations globally. Stressful working conditions, lack of organizational arrangements and lack of supporting one another at work, may contribute to increase the risk of NSIs. Methods: We conducted an observational study to analyze: 1) the effectiveness of organizational interventions to minimize the occurrence of NSIs in ED nurses; 2) to measure the impact of such interventions on the safety budget. Results: The occurrence of NSIs detected after organizational level interventions was significantly lower than the occurrence observed previously such interventions (p<0,05). By results, cost saving from managing fewer NSIs than the previous period was found. Conclusion: The study shows that the proactive, integrated and comprehensive management of organizational features at workplace brings benefits to employees and reduces the burden of the occurrence of NSIs. As result of the reduced NSIs frequency, the overall costs for follow-up of injured workers were reduced. (www.actabiomedica.it)